The stringent response plays a key role in Bacillus subtilis survival of fatty acid starvation - Pulschen, André A. (2017)
The stringent response is a universal adaptive mechanism to protect bacteria from nutritional and environmental stresses. The role of the stringent response during lipid starvation has been studied only in Gram-negative bacteria. Here, we report that the stringent response also plays a crucial role in the adaptation of the model Gram-positive Bacillus subtilis to fatty acid starvation. B. subtilis lacking all three (p)ppGpp-synthetases (RelBs, RelP and RelQ) or bearing a RelBs variant that no longer synthesizes (p)ppGpp suffer extreme loss of viability on lipid starvation. Loss of viability is paralleled by perturbation of membrane integrity and function, with collapse of membrane potential as the likely cause of death. Although no increment of (p)ppGpp could be detected in lipid starved B. subtilis, we observed a substantial increase in the GTP/ATP ratio of strains incapable of synthesizing (p)ppGpp. Artificially lowering GTP with decoyinine rescued viability of such strains, confirming observations that low intracellular GTP is important for survival of nutritional stresses. Altogether, our results show that activation of the stringent response by lipid starvation is a broadly conserved response of bacteria and that a key role of (p)ppGpp is to couple biosynthetic processes that become detrimental if uncoordinated.